E Evaluation of Bandwidth and Latency of Wireless Sensor Networks Using JPERF Simulation - Safana, Nadiatul Safana; Pazrian, Novan; Hafidha, Muhammad akhyar; Yanti, Yeni (IC-ITECHS, 2024)
WSN is a sensor network that uses wireless communication to connect sensor nodes This research discusses the evaluation of wireless sensor networks (WSN) which was a case study carried out at the Banda Aceh Mayor's Office, with a focus on measuring bandwidth and latency using the JPerf application. Testing is carried out through star topology simulation, where the server and client are connected to each other via an access point. The TCP protocol is used for bandwidth measurements, while the UDP protocol is used for latency measurements. Test results show the average bandwidth ranges from 7,518-8,029 Kbits/s with significant fluctuations due to network interference. Network latency was recorded as stable at 996 Kbits/s with low jitter. This evaluation provides recommendations for improving network performance through optimizing QoS management and strategic device placement. With this implementation, network reliability can be increased to support operational activities efficiently.